Contemporary strategy analysis : text and cases edition. - Grant, Robert M., 1948- (Hoboken : John Wiley Inc, 2016)
Brings together the text with an updated collection of 20+ case studies Introduces students to the core concepts and principles of strategy Combines a rigorous approach to business strategy analysis with highly relevant examples of current practice Includes access to high quality case and author video clips
Putting Performance Analysis into PracticeBeyond Profit: Values and Corporate Social Responsibility; Beyond Profit: Strategy and Real Options; Summary; Self-Study Questions; Notes; 3 Industry Analysis: The Fundamentals; Introduction and Objectives; From Environmental Analysis to Industry Analysis; Analyzing Industry Attractiveness; Applying Industry Analysis
Electronic reproduction.
Keywords: Business planning; Leadership; Strategic planning; Electronic books